Erythropoiesis-stimulating agents for anemic patients with cancer. Issue 6 (December 2010) - Sheikh, Semira; Littlewood, Tim J
Anemia in cancer patients is common and often associated with decreased survival and quality-of-life scores. The introduction of erythropoiesis-stimulating agents (ESAs) for the treatment of anemia in patients with solid tumors and nonmyeloid malignancies in the 1990s has proved an important alternative to red blood cell transfusions. ESAs have been consistently shown to increase hemoglobin levels and reduce transfusion requirements in anemic cancer patients whilst also being associated with improvements in quality of life. Several recent studies, however, have raised concerns about the safety of ESAs with regards to an increased number of thrombo-embolic events, decreased on-study survival and possible effects of ESAs on tumor progression. This has led to a reappraisal of the role of ESAs in the treatment of anemic cancer patients. It remains generally accepted that, if used within current guidelines and labeling recommendations, ESAs can still be considered safe in patients receiving chemotherapy once individual risks are balanced against possible benefits.